Comparative effect of human urine and ammonium nitrate application on maize (Zea mays L.) grown under various salt (NaCl) concentrations. Issue 5 (10th September 2013) - Yongha Boh, Michael; Germer, Jörn; Müller, Torsten; Sauerborn, Joachim
Abstract The present study investigates the effect of urine and ammonium nitrate on maize (Zea mays L.) vegetative growth, leaf nutrient concentration, soil electrical conductivity, and exchangeable‐cations contents under various concentrations of NaCl in a soil substrate. The experiment was arranged in a completely randomized block design with eight replications under greenhouse conditions. The experimental soil substrate was made from a 1 : 1 : 1 volume‐ratio mixture of compost, quartz sand, and silty‐loam soil. Salinity was induced by adding 0, 15, and 30 mL of 1 M NaCl solution per kg of substrate to achieve an electrical conductivity (EC) of 1.3 (S0), 4.6 (S1), and 7.6 (S2) dS m–1. Nitrogen sources were urine and ammonium nitrate applied at 180 and 360 mg N (kg soil substrate)–1. Basal P and K were added as mono potassium phosphate in amounts equivalent to 39 mg P and 47 mg K (kg substrate)–1, respectively. In the S0 treatment, a 3‐fold increase in EC was measured after urine application compared to an insignificant change in ammonium nitrate–fertilized substrates 62 d after sowing. Under saline conditions, application of 360 mg N (kg soil)–1 as urine significantly decreased soil pH and maize shoot dry weight. At the highest salt and N dose (S2, N360) 50% of urine‐fertilized plants died. Regardless of salinity there was no significant difference between the two fertilizers for investigated growth factors when N was supplied at 180 mg (kg soil)–1. Leaf N and Ca contents were higher after urine application than in ammonium nitrate–fertilized plants. At an application rate of 180 mg N (kg soil)–1, urine was a suitable fertilizer for maize under saline conditions. Higher urine‐N dosages and/or soil salinity exceeding 7.6 dS m–1 may have a deleterious effect on maize growth.